2019
DOI: 10.1080/00207454.2018.1551894
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of aerobic exercise on EEG parameters and higher cognitive functions in mild cognitive impairment patients

Abstract: Background: Mild cognitive impairment (MCI) is becoming an emerging problem for developing countries where there is an increase in expected age. There is no specific curative therapeutic treatment available for these patients. Objective: The objective of this study was to evaluate short and long-term changes in the electroencephalogram (EEG) parameters and cognition of MCI patients with aerobic exercises. Methods: A randomized controlled trial was conducted on 40 patients which were randomly divided into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 61 publications
1
62
0
8
Order By: Relevance
“…Our findings are in accordance with aerobic exercise interventions resulting in improved performance on tests of executive function in individuals with normal cognition [42,45,53,54], although contradictions have been reported [55]. A recent study reported that cognition and executive function also improved among individuals with MCI after six weeks of aerobic exercise training [56]. On the other hand, two recent six-month aerobic exercise interventions did not result in significant change in executive function among individuals with AD [48,57].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are in accordance with aerobic exercise interventions resulting in improved performance on tests of executive function in individuals with normal cognition [42,45,53,54], although contradictions have been reported [55]. A recent study reported that cognition and executive function also improved among individuals with MCI after six weeks of aerobic exercise training [56]. On the other hand, two recent six-month aerobic exercise interventions did not result in significant change in executive function among individuals with AD [48,57].…”
Section: Discussionsupporting
confidence: 88%
“…The main finding in the current study is that the amplitude of the N30 SEP peak decreased significantly after a single session of aerobic exercise in MCI patients. The beneficial effects of aerobic exercise are well established in different MCI models [ 41 , 48 , 49 ], however, to the best of our knowledge, this is the first study to explore changes in SEPs following exercise in an MCI population. The fact that even a 20-min aerobic exercise intervention yields significant changes in early SEPs suggests SEPs may be a sensitive prognostic marker for early interventions in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In total, seven studies reported on frequency analysis results in chronic exercise interventions (Tables 1, 3). Significant increases of alpha-2 (Amjad et al, 2019) and beta-3 bands (Villafaina et al, 2019) were reported, while significant decreases were found for delta (Amjad et al, 2019), and beta-1 (Amjad et al, 2019). Results by Villafaina et al were adjusted for multiple comparisons.…”
Section: Chronic Interventionsmentioning
confidence: 99%
“…Further, measurements of information flow through particular ROIs, the tendency of specific ROIs to behave as hubs for information, the connection distributions and connection strengths were similarly significantly changed within different brain networks. In another study, it was found that the approximate entropy, which is a measure of how complex a network is, was found to be increased in the eyes closed condition after a chronic exercise intervention (Amjad et al, 2019). We refer to the original studies for indepth explanations of specific measures investigated in these included studies.…”
Section: Chronic Interventionsmentioning
confidence: 99%